THE ROLE OF WOMEN IN THE DEVELOPMENT OF THE ISLAMIC ECONOMY - Ella Ariska; Nur Nafisah; Isnaini Harahap (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The development of a country cannot be separated from the role of women, even though this role cannot be seen clearly. The Estafetta of the generation of the nation's children who have good behavior and are intelligent is the main responsibility for building a country and a nation which has been carried out by women. The aims of this research include providing a description of the role of women who encourage and grow the community's economy and clearly describe the empowerment of women to fulfill their life interests and the community's economy through Sharia principles. This study uses the literature research method, which is a study in which the source of information is obtained based on literature, written works, books, or other works that are in accordance with the subject matter or problem being studied. In the results of this study, it can be concluded that the presence and role of women in developing the country's economy, especially in Indonesia, greatly impacts the quality and capability of women's position in the social environment which proves that women can and have a role in aspects of MSMEs even with big businesses. activities to empower women which become an awareness procedure and form a capacity for very large participation.